Sajmiste - Istorija jednog logora . Sajmiste - The History of a Camp - Popovic, Marko; Mitrovic, Sredjan (B 92, 2009)
Verzio FF Submission In the very heart of Belgrade on a former fairground complex, there once was a notorious camp where thousands of Jews and Serbs lost their lives during World War II. This film exposes the unknown history of one of the biggest camps in the world, presenting new documents and interpretations, exclusive testimonies of surviving witnesses, and unseen archival materials.